Evaluating the Therapeutic Potential of Duartin against Aurora A Protein Kinase in Breast Cancer Cells - Aloqbi, Akram Ahmed (International Journal of Pharmaceutical Investigation, 2025)
Background Cancer, particularly breast cancer, remains a major global health challenge, prompting ongoing research into novel therapeutic targets. This study focuses on Aurora A protein kinase, a serine/threonine kinase crucial for mitotic regulation, which is often overexpressed in various cancers, as well as breast cancer. Materials and Methods Recent study was aimed to explore the inhibitory potential of Duartin, a plant-derived isoflavonoid, against Aurora A protein kinase. Using molecular docking studies, Duartin demonstrated a high binding affinity with Aurora A, forming stable interactions with key residues, suggesting its potential as a strong inhibitor. ADMET predictions, along with PASS and Swiss Target Prediction analyses, confirmed Duartin's favorable drug-like belongings, including effective absorption, distribution, metabolism, and low toxicity. Results In vitro assays on MDA-MB-231 breast cancer cells revealed significant cytotoxic effects of Duartin, by means of an IC50 value of 13.42 µM. Additionally, time-dependent cytotoxicity assays showed sustained reduction in cell viability over 48 hr. Furthermore, treatment with Duartin significantly reduced the mRNA expression levels of Aurora A protein kinase in these cells, indicating potent inhibitory effects on its gene expression. The findings suggest that Duartin not only exhibits strong binding affinity and favourable ADMET properties but also effectively reduces cell viability and Aurora A protein kinase expression in breast cancer cells. Conclusion The outcomes of this investigation highlights Duartin’s potential as a promising therapeutic agent for breast cancer, warranting further preclinical and clinical investigations.
Keywords: ADMET predictions; Aurora A protein kinase; Breast cancer; Cytotoxic effects; Duartin; Molecular docking